Does Despotic Leadership Impact Employees' Career success: The Parallel Mediation Framework - Muhammad Naeem Sharif; Li Zhang; Mudassar Ali; Kashif Akram; Muhammad Asif (Acta Psychologica)
Drawing on the conservation of resource (COR) theory principles, this study demonstrates how despotic leadership (DL) negatively impacts employee career success (ECS) in the pharmaceutical industry. Since this is a serious growing concern in emerging research and a threat to the career therefore we aimed to investigate the relationship between (DL) and (ECS). Parallel mediating effects of job insecurity (JI) and emotional exhaustion (EE) are also tested which was overlooked in previous literature. Data were collected from 325 working employees. The target population of this study was managers, middle managers, and administrative staff facing DL. The results revealed a significant negative relationship between DL and ECS. Furthermore, JI and EE partially mediate the relationship between DL and ECS. Present research advances literature theoretically and practically in the field of organization behavior, specifically in the pharmaceutical industry. As it explored the connection between DL and employees’' career success under stressful working conditions. Thus, top management should develop leadership programs that focus on improving their behavior toward employees and leading to positive outcomes in the reduction of JI and EE. Secondly, the industry should formulate and implement clear policies and guidelines to curtail the detrimental effects of DL by inculcating open communication, employee empowerment, a supportive work environment, and shared growth of leaders and followers. Thirdly, include qualitative and quantitative methods (i.e., 360 feedback) to evaluate leaders’ behavior, which may give deeper insight into leadership behavior.